Correlation of molecular and morphologic effects of thermoembolization in a swine model using mass spectrometry imaging. (5th December 2019) - Guo, Chunxiao; Baluya, Dodge L.; Thompson, Emily A.; Whitley, Elizabeth M.; Cressman, Erik N.K.
Abstract: Hepatocellular carcinoma is a growing worldwide problem with a high mortality rate. This malignancy does not respond well to chemotherapy, and most patients present late in their disease at which time surgery is no longer an option. Over the past three decades, minimally invasive methods have evolved to treat unresectable disease and prolong survival. Intra‐arterial embolization techniques are used for large or multiple tumors but have distressingly high levels of local recurrence and can be costly to implement. A new method called thermoembolization was recently reported, which destroys target tissue by combining reactive exothermic chemistry with an extreme local change in pH and ischemia. Described herein are experiments performed using this technique in vivo in a swine model. A microcatheter was advanced under fluoroscopic guidance into a branch of the hepatic artery to deliver a targeted dose of dichloroacetyl chloride dissolved in ethiodized oil into the liver. The following day, the animals were imaged by computed tomography and euthanized. Assessing the reaction product distribution and establishing a correlation with the effects are important for understanding the effects. This presented a significant challenge, however, as the reagent used does not contain a chromophore and is not otherwise readily detectable. Mass spectrometry imaging was employed to determine spatial distribution in treated samples. Additional insights on the biology were obtained by correlating the results with histology, immunohistochemistry, and immunofluorescence. The results are encouraging and may lead to a therapy with less local recurrence and improved overall survival for patients with this disease.